Paternidad y diferencia cultural : reflexiones histórico-antropológicas para el debate (2012)
ABSTARCT: This paper asks for paternity, from a historical-anthropologic approach based on the concept of cultural diversity, proposing it like a social construction that can be re-elaborated for other familiarity modes not considered. Thus, it must be clear that those modes are not included in this work, because doing that will imply the prescription of specific types of family experiences. Avoiding prescriptions, this work present the need of keeping paternity open for different possible ways of social articulation.